Foods, nutrition and sports performance : an international scientific consensus held 4-6 February 1991 and organized by Mars, Incorporated with International Committee patronage - Williams, Clyde; Devlin, John T (E & FN Spon, 1992)
This book includes all the papers presented at the meeting, revised to take account of all the points made during discussions, and the Consensus Statement itself. The topics covered include recommendations for optimum carbohydrate, protein, fat, total energy, fluid and electrolyte, and vitamin mineral intakes to maximise sports performance.
Keywords: Food; energetický metabolismus; nutriční hodnota; tělovýchovné lékařství; Nutritive Value; Sports; Energy Metabolism; vnitřní lékařství; sporty; potraviny; nutriční terapie, dietoterapie a výživa